The arthropod Offacolus kingi (Chelicerata) from the Silurian of Herefordshire, England: computer based morphological reconstructions and phylogenetic affinities. - Sutton, MD; Briggs, D; Siveter, D; Siveter, D; Orr, P (2002)
The small, non-biomineralized, three-dimensionally preserved arthropod Offacolus kingi Orr et al. from the Wenlock Series (Silurian) of Herefordshire, England, is re-evaluated, and the new family Offacolidae erected. This new study is based on specimens which have been serially ground, reconstructed by computer and rendered in the round as coloured models. Offacolus possesses a prosomal appendage array similar to that of Limulus, but also bears robust and setose exopods on appendages II-V which are unlike those found in any other arthropods. Opisthosomal appendages are similar in number and morphology to the book-gills of Limulus. Cladistic analysis places Offacolus basally within the Chelicerata, as a sister taxon to the eurypterids and extant chelicerates, but more derived than the Devonian Weinbergina.